Seasonal and circadian activity patterns of scuttle fly assemblages (Diptera: Phoridae) in two habitats on a Mediterranean mountain - Garcia-Romera, Carlos; Barrientos, Jose (Entomologica Fennica, 2018)
Seasonal and circadian activity of scuttle fly assemblages in beech forests and highland scrublands was analysed. The scuttle flies were collected in the Montseny Natural Park (Catalonia, Spain). Seasonal fluctuations and the relation of some meteorological variables were assessed using window traps, emergence traps and pitfall traps, while circadian activity was assessed using water traps and light traps. Scuttle fly density and species richness in both habitats showed an activity peak in July. Diversity peaks were found in spring and autumn in beech forest and in summer in scrublands. Temperature was the main meteorological variable related to the seasonal dynamics of scuttle fly assemblages. We found univoltine and bivoltine species in the beech forest, while only univoltine species were found in the scrublands. Cold-adapted species were captured in winter, mainly Triphleba Rondani species. The scuttle fly circadian activity peak was at 12–15 h. Megaselia diversa (Wood, 1909) showed nocturnal or crepuscular habits.